Examining the Interrelationship between Physicochemical Properties and Brachyuran Crab Diversity in the Gulf of Kachchh, Gujarat, India: A Quadrat Sampling Approach for Ecological Assessment and Conservation Strategies - Lata, Tandel; Hitesh, Kardani; Kumar, Vijay; Jatav, Siddharth Kumar; Bhavika, Tandel (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study aims to examine the relationship between physicochemical parameters and the diversity of Brachyuran crabs in the Gulf of Kachchh, Gujarat, from November 2020 to April 2021. The research was conducted at two locations, Vador and GSFC (Gujarat State Fertilizer & Chemical Limited) Jetty near Sikka on the southern coast of the Gulf of Kachchh, using the quadrat method for sampling. Various species diversity indices and attributes were calculated, such as species diversity, richness, species evenness, density, abundance, and frequency. A total of 31 Brachyuran crabs belonging to 26 genera and 14 families were recorded, with 26 and 18 species reported from Vador and GSFC Jetty sites, respectively. The Portunidae family had the highest number of species, followed by the Xanthidae family. Brachyuran crab species were found in habitats including rocky areas, muddy areas, mangroves, sponge-associated areas, seaweed-associated areas, and coral reef-associated areas. During the study period, Thalamita crenata showed the highest average density (no/m2) and abundance along the Sikka coast. An analysis of physicochemical parameters, including air and water temperature, pH, salinity and dissolved oxygen, revealed positive correlation with temperature and salinity and a negative correlation with dissolved oxygen. These findings provide crucial baseline data that can inform the development of conservation and biodiversity management strategies in this region, emphasizing the importance of protecting coastal ecosystems.